(untitled) (Journal of Patan Academy of Health Sciences, 2019)
Introductions: Perinatal mortality rate (PMR) of Nepal is 31 deaths per 1000 pregnancies and neonatal mortality rate (NMR) is 21 deaths per 1000 live births according to Nepal Demographic and Health Survey (NDHS) 2016. This study aims to analyse the trend of PMR and NMR of babies delivered at Patan hospital, Nepal. Methods: This was a retrospective study done in the department of Pediatrics to analyse the trend of neonatal and perinatal outcome of babies delivered during three years from April 2016 to March 2019 at Patan Hospital, Patan Academy of Health Sciences, Nepal. Data was collected from hospital records and perinatal audit. The mode of delivery (vaginal, instrumental, caesarian), birth status (sex, premature, still, live, APGAR, birth weight) and final outcome (neonatal and perinatal mortalities) were analyzed descriptively using Microsoft Excel 2010. Results: The final outcome of total 22937 deliveries during three years were PMR 4.34, corrected PMR 10.85 per 1000 total births and NMR 3.62 per 1000 live births. There were 22913 (99%) live births, 3090 (13.3%) had low birth weight, 11898 (52%) spontaneous vaginal delivery, 10700 (47%) cesarean and 339 (1.5%) instrumental deliveries. Conclusions: The overall PMR was 4.34 per 1000 total births and NMR was 3.62 per 1000 live births at Patan Hospital.